Polish immigration in Belgium since 2004: New dynamics of migration and integration? - Levrau, François; Piqueray, Edith; Goddeeris, Idesbald; Timmerman, Christiane (Ethnicities, 2014)
Belgium has been a traditional destination for Polish immigrants since the 19th century. In the period after the fall of the Iron Curtain, Polish migration to Belgium was largely characterized by pendulum movements and illegal stays, but following Poland's accession to the EU in 2004, the Belgian labour market was gradually opened to Polish citizens. To date, this new situation has not been the subject of research, and we therefore present the first analysis of the impact of EU enlargement on Poles in Belgium. By means of semi-structured interviews with both Polish key informants and Polish families, we illustrate the extent to which Polish migration and integration patterns have changed. Our results lead us to conclude that Poles are increasingly opting for longer and more permanent stays, which means that Polish migration no longer follows the pendulum pattern. Although this implies increased orientation toward Belgian society, it does not entirely preclude any attachment to Polish culture and identity. This confirms a widely accepted insight from migration studies: the desire to integrate in structural societal spheres does not reduce the importance that migrants attach to aspects they consider crucial to staying in touch and identifying with their regions of origin.